KAJIAN HUKUM TERHADAP PENERTIBAN VILLA TANPA IJIN DI KOTA DENPASAR - Pande Made Briyanco Bali; I Nyoman Suandika; Kadek Dedy Suryana (Yayasan Nusantara Hasana Berdikari, 2025)
Bali is a province in Indonesia with unique characteristics that contribute to regional development, where economic pillars are built on the strengths of the tourism sector. Its rich natural and cultural potential supports sustainable tourism development. Its extraordinary natural beauty and unique cultural heritage make Bali one of the most popular tourist destinations in Indonesia. This is supported by Tourism Minister Arief Yahya, who stated that Bali is a destination already well-known on the global tourism map. Therefore, Bali is highly deserving of being an icon of Indonesian tourism.